Practical Aspects of Declarative Languages : 22nd International Symposium, PADL 2020, New Orleans, LA, USA, January 20-21, 2020, Proceedings /: 22nd International Symposium, PADL 2020, New Orleans, LA, USA, January 20-21, 2020, Proceedings. (2020) - Unknown
No abstract available